Does vitamin A rich orange-fleshed sweetpotato adoption improve household level diet diversity? Evidence from Ghana and Nigeria - Adekambi, S.; Okello, J.J.; Low, Jan W.; Abidin, P.E.; Carey, E.E. (Informa UK Limited, 2023)
Promoting the consumption of locally available food crops such as orange-fleshed sweetpotato (OFSP) that are rich in beta carotene, a precursor for vitamin A, has been shown to be a highly effective means of fighting against vitamin A deficiency at the community level when combined with nutrition education. After a three-year intervention promoting OFSP uptake using different market-led approaches, a structured survey was conducted among 204 participant and 422 non-participant households in Ghana and Nigeria in 2017. In this study, we test whether the adoption of OFSP has a significant effect on dietary diversity, using a counterfactual approach based on the conditional independence-based estimators of average treatment effect techniques. Results found that household, young child and woman's dietary diversity scores increased when households adopted OFSP varieties. However, the positive effects of OFSP adoption on household dietary diversity only occurred in the Ghanaian sub-sample, not the Nigerian. Policymakers and development support partners should ensure institutional support in terms of intensive campaigns to sensitize farmers and their families about the benefits of these crops in order to create and sustain demand for biofortified foods as a means of fighting micronutrient malnutrition.